PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN YANG DIMEDIASI OLEH CITRA PERUSAHAAN - Luki Kusuma; Salma Saleh; Sinarwati Sinarwati (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
The objective of this research is to find out the effect of service quality and company image on customer satisfaction and also to see the effect of mediation of corporate image on the correlation between service quality and customer satisfaction of Wakatobi Regency PDAM.This research was conducted at Wakatobi Regency PDAM using quantitative approach. The population of this study is 4974 and the sample used is 155 people with purposive sampling technique. Data was collected using questionnaires and analyzed using structural equation modeling (SEM).The result of this research concludes that service quality has positive and significant effects on customer satisfaction, service quality has positive and significant effects on corporate image, corporate image has positive and significant effects on customer satisfaction and the corporate image partially mediates the correlation between service quality and customer satisfaction at Wakatobi Regency PDAM.Keywords: service quality, corporate image, and consumer satisfaction.